2003
DOI: 10.1038/sj.jhh.1001536
|View full text |Cite
|
Sign up to set email alerts
|

Night-time blood pressure load is associated with higher left ventricular mass index in renal transplant recipients

Abstract: The absence of nocturnal fall in blood pressure (BP) is named as nondipper status, which has been shown to be an additional risk factor for the development of left ventricular hypertrophy and cardiovascular events in several high-risk groups. The aim of this study was to determine the influences of the nondipper status and nocturnal blood pressure loads on left ventricular mass index (LVMI) in renal transplant recipients. A total of 35 nondiabetic renal transplant recipients were included into the study. A 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
0
28
3
2
Order By: Relevance
“…23,24 The majority of patients with uncomplicated hypertension experience a fall in their nighttime BP of Ͼ10% of the daytime mean arterial BP. The absence of a fall in nocturnal BP has been linked to target organ damage, such as carotid artery structural alterations and LVH in some studies [25][26][27][28][29] but not others. 30,31 Observational studies have shown that hypertensive patients with elevated nighttime BP are at greater risk for experiencing cardiovascular outcomes and stroke compared with hypertensive patients with a normal decrease in nocturnal BP.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The majority of patients with uncomplicated hypertension experience a fall in their nighttime BP of Ͼ10% of the daytime mean arterial BP. The absence of a fall in nocturnal BP has been linked to target organ damage, such as carotid artery structural alterations and LVH in some studies [25][26][27][28][29] but not others. 30,31 Observational studies have shown that hypertensive patients with elevated nighttime BP are at greater risk for experiencing cardiovascular outcomes and stroke compared with hypertensive patients with a normal decrease in nocturnal BP.…”
Section: Discussionmentioning
confidence: 99%
“…The non-dipper status is also common in renal transplant recipients [35]. Lipkin et al [36] studied 28 normotensive renal transplant recipients, of whom 16 were on cyclosporine-based and 12 were on azathioprine-based immunosuppressive regimen.…”
Section: Non-diabetic Patientsmentioning
confidence: 98%
“…Is the loss of circadian BP rhythm a pathogenic factor involved in allograft function loss? Loss of circadian BP changes has been linked to target organ damage and accelerated kidney function loss in hypertensive patients with and without CKD (9,33,34). Although uncontrolled systemic hypertension is related to poor allograft and patient survival after kidney transplantation, loss of normal nocturnal fall in SBP, independent of BP control, has not been fully defined as a promoter of kidney function attrition after transplantation (2,35,36).…”
Section: Discussionmentioning
confidence: 99%